Psychopathological consequences related to COVID-19 infection: The most relevant reactions of the general population. (13th April 2021) - Serafini, G.; Aguglia, A.; Amerio, A.; Sher, L.; Amore, M.
Abstract : Introduction: As a result of the emergence of coronavirus disease 2019 (COVID-19) outbreak caused by acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in the Chinese city of Wuhan, a situation of socio-economic crisis and profound psychological distress rapidly occurred worldwide. Objectives: This work aimed to comprehensively review the current literature about the impact of COVID-19 infection on the mental health in the general population. Methods: A detailed review has been conducted in order to identify the main psychopatological consequences related to Covid-19 infection in the general population. Results: Various psychological problems and important consequences in terms of mental health including stress, anxiety, depression, frustration, uncertainty during COVID-19 outbreak emerged progressively. The psychological impact of quarantine related to COVID-19 infection has been additionally documented together with the most relevant psychological reactions in the general population related to COVID-19 outbreak. Conclusions: The role of risk and protective factors against the potential to develop psychiatric disorders in vulnerable individuals with Covid-19 infection need to be carefully addressed in the clinical practice.